2002
DOI: 10.1519/1533-4287(2002)016<0599:eotbpf>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the BOD POD for Estimating Percent Fat in Female College Athletes

Abstract: The purpose of this investigation was to examine the accuracy of percent body fat (%BF) estimates obtained by air displacement plethysmography (ADP) using the BOD POD Body Composition System compared with hydrostatic weighing (HW) in a group of female college athletes (n = 80). In addition, %BF estimates by skinfold measures (SF) were also obtained for comparison. A lean subset (n = 39) of the sample was also examined. Mean %BF estimated for the entire sample by ADP (21.2 +/- 5.9%) was significantly greater th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 0 publications
2
14
0
1
Order By: Relevance
“…The BOD POD ® S / T, however, provided reliable % BF values within-and between-days amongst the sample male and female subjects. Generally, fi ndings from the current study both contrast [3,4] and concur [14,20,21] with the literature examining the validity and reliability values between the BOD POD ® and other forms of body composition assessment tools (e. g., hydrodensitometry and skinfolds). While the authors of this paper could specifi cally reiterate the vast comparative BOD POD ® literature [2,5,6,11,16,22] , this would, however, not serve to support the impetus of the investigation, which was to determine the validity and reliability of the BOD POD ® S / T assessment tool, not its parentcounterpart, the BOD POD ® .…”
Section: Discussion ▼supporting
confidence: 85%
“…The BOD POD ® S / T, however, provided reliable % BF values within-and between-days amongst the sample male and female subjects. Generally, fi ndings from the current study both contrast [3,4] and concur [14,20,21] with the literature examining the validity and reliability values between the BOD POD ® and other forms of body composition assessment tools (e. g., hydrodensitometry and skinfolds). While the authors of this paper could specifi cally reiterate the vast comparative BOD POD ® literature [2,5,6,11,16,22] , this would, however, not serve to support the impetus of the investigation, which was to determine the validity and reliability of the BOD POD ® S / T assessment tool, not its parentcounterpart, the BOD POD ® .…”
Section: Discussion ▼supporting
confidence: 85%
“…However, the results of the present study highlight the differences between ADP and BIA compared to different skinfold equations, with the least variation reported between ADP and the Jackson & Pollock (1978) and Jackson et al (1980) skinfold equations compared to BIA and the Durnin & Womersley (1974) skinfold equation. Previous evidence has reported accurate % BF estimations when using skinfold equations compared to ADP and HW (Vescovi et al, 2002). However, in contrast, Kilduff et al (2007) indicated that between-day differences using the Jackson & Pollock (1978) equation where not within the acceptable limits compared to ADP, BIA and HW.…”
Section: Jacksonmentioning
confidence: 83%
“…For this two-component method, body density depends on the given athlete having both normal BMD as well as a normal hydration status at the time of measurement. Variation in both areas can influence the fat free component and this is well documented in athletes,13 14 thus limiting the use of ADP and other densitometry techniques such as underwater weighing for the athletic population 2…”
Section: Discussionmentioning
confidence: 99%